Interaction between COX-1 and COX-2 increases susceptibility to ischemic stroke in a Chinese population - Zhao, Lei; Fang, Jinghuan; Zhou, Muke; Zhou, Jie; Yu, Lihua; Chen, Ning; He, Li (BMC neurology, 2019)
Mutations of cyclooxygenase gene (COX gene) may increase the susceptibility of ischemic stroke. We investigated five variants (rs5788, rs1330344, rs3842788, rs20417, and rs689466) of two COX genes in order to explaining the association between these polymorphisms and we also investigated the association between these variants and ischemic stroke risk to determine whether gene-gene interaction between these genes increases the susceptibility of ischemic stroke or its subtypes. A total of 1981 study subjects (1078 cases and 903 control subjects) were recruited. The interaction of multiple factors was investigated using Multifactor Dimensionality Reduction. The additive effect of single nucleotide polymorphisms on ischemic stroke or its subtypes were analyzed by multiple factor logistic regression. At COX-1(rs1330344), AA genotype carriers had a lower susceptibility of ischemic stroke (OR = 0.657, 95%CI = 0.437-0.988, P = 0.044), and A allele carriers had a lower susceptibility of ischemic stroke (OR = 0.812, 95%CI = 0.657-0.978, P = 0.029). At COX-1(rs3842788), AA genotype carriers had a higher susceptibility of ischemic stroke (OR = 5.203, 95% CI = 1.519-5.159, P = 0.016). At COX-2 (rs689466), AA genotype carriers had a higher susceptibility of large-artery atherosclerosis (OR = 1.404, 95% CI = 1.019-1.934, P = 0.038). COX-1(rs1330344, rs3842788) and COX-2 rs689466 interacted in SVO, but had no additive effect with ischemic stroke and other subtypes. At rs1330344, AA genotype may reduce the susceptibility of ischemic stroke. At rs3842788, AA genotype may increase the susceptibility of ischemic stroke. At rs689466, AA genotype may increase the susceptibility of large-artery atherosclerosis (LAA). COX - 1(rs1330344, rs3842788) and COX-2 rs689466 interacted in small vessel occlusion (SVO), but had no additive effect with ischemic stroke and other subtypes.